Governmental Strategies For Enhancing The Competitiveness Of Small And Medium Enterprises In Algeria - Bouakel, Mustapha (جامعة الوادي - University of Eloued, 2019)
This study aims to analyse the governmental strategies for enhancing the competitiveness of SMEs in Algeria, using a survey contained 89 SMEs from six wilaya, and the collected data was processed by SPSS 24 Program. The study concluded that the construction of a competitive and integrated institutional fabric requires more focus on developing entrepreneurship spirit, the promotion of subcontracting and integration between the support organs and economic sectors, in addition to the strengthen of investment in the quality, knowledge and innovation entrances
مقال
Keywords: Competitiveness ; SMEs ; Rehabilitation ; Support